Impelentasi Model Pembelajaran Kooperatif Example Non Example untuk Meningkatkan Hasil Belajar Matematika Tentang Satuan Waktu Kelas III SD Negeri Bugangan 03 Semarang - Ismariyono Ismariyono (Jurnal Inovasi Pembelajaran di Sekolah, 2023)
The problem that the Class III teacher at SD N Bugangan 03 complained about in Mathematics was the low score in Mathematics, especially on the Unit of Time. This is evidenced by the holding of an initial test of students' abilities in learning Mathematics regarding "Time Units" which is still low, namely out of 31 students only 13 students (41.94%) scored above 76 (above KKM). So one of the efforts that can be made in learning Mathematics is through example non-example learning. This research is a classroom action research that aims to improve learning mastery and student learning outcomes through the Example non Example cooperative learning model in the Mathematics subject about Class III Semester 2 Semester 2 SD N Bugangan 03 academic year 2021/2022. The subjects in this study were 31 students of Class III. This research is a classroom action research which consists of 2 cycles. The instrument used in data collection was a written test. The results of the study: (1) The use of the example non example type of cooperative learning model can improve learning outcomes, as evidenced by the increase in student learning at an average pre-cycle of 69.14. In the first cycle the average is 74.64, and in the second cycle the class average is 81.71; (2) The use of an example non example type of cooperative learning model can increase the completeness of learning outcomes, as evidenced by an increase in student learning completeness at pre-cycle 39.29%. In the first cycle the classical learning mastery was 71.43% and in the second cycle the classical learning mastery was 85.42%. The success of this study was the achievement of success indicators of 85.42% > 75% of the number of students who achieved the Minimum Completeness Criteria (KKM). In conclusion, the implementation of the example non-example learning model can improve mathematics learning outcomes.